Upper Limb Changes in DMD Patients Amenable to Skipping Exons 44, 45, 51 and 53: A 24-Month Study - Claudia Brogna; Marika Pane; Giorgia Coratti; Adele D'Amico; Elena Pegoraro; Luca Bello; Valeria Ada Maria Sansone; Emilio Albamonte; Sonia Messina; Antonella Pini; Maria Grazia D'Angelo; Claudio Bruno; et al. (MDPI AG, 2023)
Introduction: The Performance of Upper Limb version 2.0 (PUL 2.0) is increasingly used in Duchenne Muscular Dystrophy (DMD) to study longitudinal functional changes of motor upper limb function in ambulant and non-ambulant patients. The aim of this study was to evaluate changes in upper limb functions in patients carrying mutations amenable to skipping exons 44, 45, 51 and 53. Methods: All DMD patients were assessed using the PUL 2.0 for at least 2 years, focusing on 24-month paired visits in those with mutations eligible for skipping exons 44, 45, 51 and 53. Results: 285 paired assessments were available. The mean total PUL 2.0 12-month change was −0.67 (2.80), −1.15 (3.98), −1.46 (3.37) and −1.95 (4.04) in patients carrying mutations amenable to skipping exon 44, 45, 51 and 53, respectively. The mean total PUL 2.0 24-month change was −1.47 (3.73), −2.78 (5.86), −2.95 (4.56) and −4.53 (6.13) in patients amenable to skipping exon 44, 45, 51 and 53, respectively. The difference in PUL 2.0 mean changes among the type of exon skip class for the total score was not significant at 12 months but was significant at 24 months for the total score (p < 0.001), the shoulder (p = 0.01) and the elbow domain (p < 0.001), with patients amenable to skipping exon 44 having smaller changes compared to those amenable to skipping exon 53. There was no difference within ambulant or non-ambulant cohorts when subdivided by exon skip class for the total and subdomains score (p > 0.05). Conclusions: Our results expand the information on upper limb function changes detected by the PUL 2.0 in a relatively large group of DMD patients with distinct exon-skipping classes. This information can be of help when designing clinical trials or in the interpretation of the real world data including non-ambulant patients.